2017
DOI: 10.1210/jc.2017-02381
|View full text |Cite
|
Sign up to set email alerts
|

A 6-Year Follow-Up of Fracture Incidence and Volumetric Bone Mineral Density Development in Girls With Turner Syndrome

Abstract: Current pediatric TS patients that are treated with growth hormone and estrogens are not at risk for osteoporotic fractures. Low BMD in TS may be counterweighted by enlarged bone radius, which leads to normal bone strength at the appendicular skeleton.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 28 publications
2
15
0
Order By: Relevance
“…The forearm or upper limb appear to be the most commonly fractured sites in women with TS in this study as in others, 6,12,13 especially those assessing children 10,15 Interestingly, forearm fractures were also common in POI, so this may not be a TS specific observation but studies disagree on this point. 15,16 Forearm fractures are more common than other fractures in normal school-aged children, 35,36 and so we conclude that the forearm fracture frequency observed in the current cohort of women with TS and POI may be similar to that of the general population. The increased bone porosity and the deficit in bone mass compared to longitudinal growth that occurs at peak height velocity during puberty may explain the increased fracture incidence in this age group.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…The forearm or upper limb appear to be the most commonly fractured sites in women with TS in this study as in others, 6,12,13 especially those assessing children 10,15 Interestingly, forearm fractures were also common in POI, so this may not be a TS specific observation but studies disagree on this point. 15,16 Forearm fractures are more common than other fractures in normal school-aged children, 35,36 and so we conclude that the forearm fracture frequency observed in the current cohort of women with TS and POI may be similar to that of the general population. The increased bone porosity and the deficit in bone mass compared to longitudinal growth that occurs at peak height velocity during puberty may explain the increased fracture incidence in this age group.…”
Section: Discussionsupporting
confidence: 50%
“…4,6,[10][11][12][13][14] An increased risk for fractures in women or girls with TS was noted in several reports 3,4,[13][14][15] but not in others. 11,16 A recent patient survey observed an increased fracture risk in women with TS only above the age of 45. 10 Such discrepancies can be accounted for by different methodologies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also found that while the overall fracture frequency was not increased, adolescent girls with TS reported more forearm fractures than non‐TS peers. In comparison, a recent European study found long bone fractures were not more common in girls with TS compared to healthy controls . Annual fracture incidence in controls was estimated from hospitalizations for fracture during the same time period, which the authors suggest likely under‐represents actual fractures.…”
Section: Discussionmentioning
confidence: 90%
“…Decrease in both cortical bone and trabecular bone occurs in adolescents and young adults with Turner syndrome (Holroyd et al, ; Soucek et al, ). However, high‐resolution pQCT (hr‐pQCT) has shown normal cortical bone in adolescents with Turner syndrome (Soucek, Schonau, Lebl, & Sumnik, ), and a prospective study of children with Turner syndrome hr‐pQCT showed a decrease in BMD Z‐score with time, but no increased risk of fracture at this age (Soucek et al, ). An earlier study of adults showed clearly reduced cortical porosity at both tibial and radial sites, as well as compromised trabecular integrity at both sites, leading to compromised trabecular microarchitecture and lower bone strength, both of which lead to a higher risk of low‐impact fractures (Hansen, Brixen, & Gravholt, ).…”
Section: Endocrine Issuesmentioning
confidence: 99%